Exploring women’s empowerment in livestock: A qualitative study in Caquetá, Colombia - Rodriguez, Luz A.; Vanegas Cubillos, Martha; Buitrago, Juliana; Mesa, Aana María; Santamaria Ruiz, Juliana; Correal, Antonia (2024)
This report presents the results of applying the qualitative protocols of the Women’s Empowerment in Agriculture Index (WEAI) in La Montañita, Caquetá, Colombia, with women’s associative groups in livestock farming. The research explores how participatory approaches can integrate women’s empowerment and promote gender equality in developing climate-resilient, low-emission food systems. It specifically examines the role of women’s organizations in the livestock sector and the structural barriers to their collective empowerment. The findings show that women in La Montañita view empowerment as a shift from dependency to economic and social independence, facilitated by their participation in associations. These associations provide access to resources, income control, and leadership opportunities, enabling women to transform traditional gender roles. Despite progress, women face a "triple burden" of domestic, productive, and community roles, limiting their economic and political participation. Poor road conditions and limited mobility further restrict their access to training and decision-making spaces. While women recognize the impacts of climate change, they do not see them as gendered, though existing literature highlights their greater vulnerability due to limited access to resources and decision-making power. Women are implementing strategies like silvopastoral systems and agroforestry to adapt to climate change, although these strategies add to their workload. Supporting women’s leadership in climate change adaptation is essential for improving resilience at the household and community levels. Women’s active participation in local associations plays a critical role in building resilience to climate-related challenges in the region.